The Analysis of Population Aging Phenomena in Poland in Spatial Perspective - Justyna Wilk; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2014)
The processes of socio-economic development are continuously accompanied by the process of population aging. It is seen as a growing of the percentage share of people aged 65 and over in the general population. It covers the majority of European Union countries and also refers to Poland. The objective of the paper is to analyze the population aging phenomenon in spatial perspective. The study was carried out for 66 subregions (NUTS 3) and covered the period 1995-2012. Poland is characterized by a strong spatial diversification regarding the senior citizens share and its growth rate, and also determinants exerting impact on the demographic aging processes. The demographically youngest and slowest aging population lives in south-eastern and also central Poland. The most intensive population aging processes are seen in the selected subregions of south-western Poland. Here, we observe extremely low fertility, demographically old working-age population and also significant migration outflow of younger people.
Keywords: C38; C51; J11; 330; population aging; socio-economic development; spatial approach; taxonomic analysis; regression analysis